1997
DOI: 10.1097/00006123-199704000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cranial Surface Anatomic Fiducials for Interactive Image-guided Navigation in the Temporal Bone: A Cadaveric Study

Abstract: Interactive image-guided navigation in the temporal bone is possible with registration of cranial surface anatomic fiducials. It may be useful to the neurosurgeon and otologist in identifying critical anatomic structures of the temporal bone encountered during the translabyrinthine, retrolabyrinthine presigmoid, and suboccipital approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 28 publications
1
40
0
5
Order By: Relevance
“…Only the cadaveric study by Vrionis et al [14] reported a target localization error well within the range of SM with 0.91 mm to 2.44 mm for superficial and 0.71 mm to 1.52 mm for deep temporal structures using 1-mm-thick CT slices.…”
Section: Discussionmentioning
confidence: 97%
“…Only the cadaveric study by Vrionis et al [14] reported a target localization error well within the range of SM with 0.91 mm to 2.44 mm for superficial and 0.71 mm to 1.52 mm for deep temporal structures using 1-mm-thick CT slices.…”
Section: Discussionmentioning
confidence: 97%
“…TRE(r) with anisotropic noise covariance 27 can be predicted as (5) δ ij is the Kronecker delta, ε the smallness parameter of the perturbation-theoretic approach, are the components of the FLE covariance matrix Σ FLE , r i are the coordinates of a point r expressed in the principal axes coordinate system of the fiducials; are the i-th singular values of the fiducial configuration in the principal axes. The RMS(TRE) can be measured and pre dicted 34 via (6) This quantity is accessible via repetitions of measurements and includes the uncertainty of the tip of a navigated probe, p r , RMS TRE probe (probe tip, p r ) relative to an uncertain Dynamic Reference Frame (DRF), and RMS TRE DRF (p p ) 34 in quadrature via (7) None of the in vitro studies that we are aware of 15,[34][35][36][37][38][39][40] is providing data on the experimental User Localization Error (ULE) and none compares measurements with predictions of application accuracy 25,34,[41][42][43] . The present experiments close this gap by mimicking a clinical setting and by exploiting all available information provided by an open-source navigation system.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 99%
“…Furthermore, imagedata-based navigation plays an ever-increasing role in cases of minimally invasive surgery (Vrionis et al, 1997;Alp et al, 1998;Maurer et al, 1998;Steinmeier et al, 2000;Hoffmann et al, 2002). Many studies demonstrated that the precision of placing instruments and screws can be optimized with modern navigation systems (Wagner et al, 1995;Vaughan, 1996;Millesi et al, 1997;Vrionis et al, 1997;Alp et al, 1998;Maurer et al, 1998;Hassfeld and Mühling, 2000;Steinmeier et al, 2000;Gaggl et al, 2001;Hassfeld and Mühling, 2001;Siessegger et al, 2001;Watzinger et al, 2001;Pott and Schwarz, 2002;Wagner et al, 2002;Wanschitz et al, 2002). Of particular note are recent advances in CT-data-based diagnostics, computer-assisted planning facilities and navigation technology which improve the outcome of surgical procedures (Vrionis et al, 1997;Maurer et al, 1998;Pott and Schwarz, 2002).…”
Section: Introductionmentioning
confidence: 99%